1996
DOI: 10.1007/s002239900144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indomethacin Administration on Bone Turnover and Bone Mass in Adjuvant-Induced Arthritis in Rats

Abstract: We examined the bone turnover and bone mass in adjuvant-induced arthritis in rats and assessed the effects of indomethacin in this model. One hundred ten SD rats, 6 weeks of age, were assigned to 11 groups and injected with adjuvant or solvent in the right foot. Adjuvant-injected rats were orally administered indomethacin at doses of 0 (vehicle), 0.1 (low), 0.5 (medium), and 1.5 (high) mg/kg body weight from the start (day 0). Animals were sacrificed on days 0, 14 (acute phase), and 28 (chronic phase). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Using an adjuvant arthritis rat model, Xu et al [1996] found that OCs in normal bone express both IL-1R1 and IL-1R2, while OCs in arthritic bone primarily expressed the type I receptor. Assuming that based on the evidence by others [Aota et al, 1996] that OCs in arthritic bone are larger [not reported by Xu et al, 1996], these results would be similar to ours. Our results also parallel those of Wei et al [2005] who showed increased IL-1R1 RNA expression and decreased IL-1R2 expression in bone marrow macrophages differentiated over 4 days of exposure to RANKL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using an adjuvant arthritis rat model, Xu et al [1996] found that OCs in normal bone express both IL-1R1 and IL-1R2, while OCs in arthritic bone primarily expressed the type I receptor. Assuming that based on the evidence by others [Aota et al, 1996] that OCs in arthritic bone are larger [not reported by Xu et al, 1996], these results would be similar to ours. Our results also parallel those of Wei et al [2005] who showed increased IL-1R1 RNA expression and decreased IL-1R2 expression in bone marrow macrophages differentiated over 4 days of exposure to RANKL.…”
Section: Discussionsupporting
confidence: 91%
“…Depending on the species, OCs involved in normal bone remodeling contain on average 3-10 nuclei [Piper et al, 1992]. In disease states involving pathological bone loss such as inflammatory arthritis, periodontal disease and Paget's disease, large OCs predominate in the areas of excessive resorption [Arend and Dayer, 1990;Aota et al, 1996;Singer and Roodman, 1996;Smith et al, 1997]. In Paget's disease, OCs have been detected that were 100 mm in diameter and contained up to 100 nuclei [Singer and Roodman, 1996].…”
mentioning
confidence: 99%
“…The extract, as evidenced from radiological indices (Table 1), at doses of 10 mg kg -1 and 300 mg kg -1 protected against bone loss due to reduced bone formation and increased resorption which are the causes of bone loss in adjuvant-induced arthritis in rats (Aota et al, 1996;Findlay and Haynes, 2005). It is doubtful if this effect is mediated by an immunologic protection of the bones.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies have shown that intraplantar injection of carrageenan in the 7-day-old chick elicits a quantifiable, reliable and relatively short lasting state of oedema, that is differentially attenuated by the administration of typical antiinflammatory compounds (Roach and Sufka, 2003). The rat adjuvant arthritis on the other hand, is the most frequently used model of chronic inflammation for screening NSAIDs, steroids and immunosuppressive drugs (Weichman, 1989;Crofford et al, 1992;Aota et al, 1996).…”
Section: Discussionmentioning
confidence: 99%